Imagining the Jewish future : essays and responses - Teutsch, David A., 1950- (Albany : State University of New York Press, 1992)
Annotation Feminism and religious language, the relationship between Israelis and American Jews, and the interaction between the family and the synagogue are among the topics of the dozen essays from a conference sponsored by the Reconstructionist Rabbinical College (no date or location noted) and responses to them. Some make actual predictions; others note trends, or simply identify important issues. No index. Paper edition (unseen), $19.95. Annotation copyright by Book News, Inc., Portland, OR.
God, prayer, and religious language -- Tradition and religious practice -- Jewish education : crisis and vision -- Creativity and community : the Jewish artist's experience -- Jewish literacy : will more and more be known by fewer and fewer? -- Are American and Israeli Jews drifting apart? -- Facing the Jewish future -- Jewish family ethics in a post-halakhic age -- The coming reformation in American Jewish identity -- Social justice : reenvisioning our vision -- The Synagogue and caring community -- Theology and community.
Includes bibliographical references (pages 269-276).
Print version record.
JSTOR
Keywords: Judaism -- United States -- Forecasting -- Congresses; Jews -- United States -- Intellectual life -- Forecasting -- Congresses; Jews -- United States -- Attitudes toward Israel -- Forecasting -- Congresses; Israel and the diaspora -- Forecasting -- Congresses; Jews -- United States -- Social conditions -- Forecasting -- Congresses; Judaïsme -- États-Unis -- Prévision -- Congrès.; Juifs -- États-Unis -- Vie intellectuelle -- Prévision -- Congrès.; Juifs -- États-Unis -- Attitudes envers Israël -- Prévision -- Congrès.; Israël et la diaspora -- Prévision -- Congrès.; Juifs -- États-Unis -- Conditions sociales -- Prévision -- Congrès.; RELIGION -- Judaism -- History; Israel and the diaspora -- Forecasting; Jews -- Attitudes toward Israel -- Forecasting; Jews -- Intellectual life -- Forecasting; Jews -- Social conditions -- Forecasting; Judaism -- Forecasting; United States; Conference papers and proceedings